Krieg und Geschlecht im 20. Jahrhundert: Interdisziplinäre Perspektiven zu Geschlechterfragen in der Kriegsforschung - Altieri, Riccardo; Streichhahn, Vincent (transcript, 2021)
An interdisciplinary examination of the complex relationship between war and gender in the 20th century.